'Capital account liberalisation and exchange rate regimes - options for the small open economy' - Demeritte, Kevin (Caribbean Centre for Money & Finance [St. Augustine]TT, 2002)
Looks at issues related to the liberalization of the capital account, in the context of a small open economy such as The Bahamas.